Dietary habits and obesity indices in patients with gastro-esophageal reflux disease: a comparative cross-sectional study - Omid Eslami; Mansour Shahraki; Ali Bahari; Touran Shahraki (BMC Gastroenterology, 2017)
Abstract Background Gastro-esophageal reflux disease (GERD) is suggested to be associated with some socio-demographic and lifestyle factors. Although the roles of some factors such as obesity are well documented, evidence on the impact of other factors such as dietary habits are still inconclusive. The aim of this study was to determine the relationship between socio-demographic and lifestyle factors with GERD in participants referred to a teaching hospital in Zahedan, South-East of Iran. Methods This comparative cross-sectional study was conducted during 2014–2015. All patients completed a structured questionnaire regarding information on socio-demographic status, lifestyle factors and dietary habits. Anthropometric indices including body mass index (BMI) and waist circumference (WC) were used to determine general and central obesity, respectively. Data were analyzed using SPSS software version 22. Value of p < 0.05 was considered as statistically significant. Results Five hundred and five participants, including 285 GERD and 220 Non-GERD participants participated in the study. In univariate analysis, being married (OR = 1.57, 95%CI = 1.04, 2.36), general obesity (OR = 1.77, 95%CI = 1.11, 2.81), central obesity (OR = 2.09, 95%CI = 1.46,3.01) and consumption of citrus fruits between meals (OR = 1.69, 95%CI = 1.04, 2.73) were associated with higher odds of GERD, while higher educational level (OR = 0.53, 95%CI = 0.36,0.77) and regular physical activity ≥2 h/week (OR = 0.53, 95%CI = 0.30, 0.94) were associated with lower odds of GERD. In the adjusted model, central obesity (OR = 1.88, 95%CI = 1.18, 3.01) and consumption of citrus fruits between meals (OR = 2.22, 95%CI = 1.30, 3.81) were positively associated with odds of GERD, while higher educational level (OR = 0.55, 95%CI = 0.33, 0.91) was associated with decreased odds of GERD. Conclusion According to the results of the current study, central obesity as determined by WC and citrus fruit intake were independent factors associated with GERD. Therefore, lifestyle modification might have a positive effect in the treatment of GERD in an urban population of Iran.